Perbandingan Sistem Pengelolaan Sampah di Indonesia dan Korea Selatan: Kajian 5 Aspek Pengelolaan Sampah - Hendra, Yulia (Jurnal Aspirasi, 2016)
Government of Indonesia still faces many challenges in the implementation of waste management systems, especially in order to achieve the universal access target on sanitation by 2019, such as: low of services access , low public awareness of practicing good hygiene and healthy, low commitment of the local government for waste management, weak institutional management of sanitation (regulator and operator), and also lack of human resources. The Indonesian government needs to learn from other countries that have been succeed in the implementation of environmentally friendly waste management system. One of the countries that have been a success in managing waste is the government of South Korean. The study was conducted to compare the waste management in Indonesia and South Korea views from 5 aspects of waste management, namely: institutional aspects, financial aspects, regulatory aspects, public participation, aspects and technical aspects of the operations. The study was conducted by studying the literature and observation directly to South Korea. The research resulted that waste management systems in Indonesia is still behind compared to South Korea, both in institutional, human resources, budget, law enforcement, and public and private participation. Full commitment of all relevant stakeholders is a key factor in the success of building an integrated and environmentally friendly waste management system.  Pemerintah Indonesia masih menghadapi banyak kendala dalam penyelenggaraan sistem pengelolaan sampah, terutama dalam rangka pencapaian target universal akses bidang sanitasi pada tahun 2019, antara lain: masih rendahnya akses pelayanan sampah, masih rendahnya kesadaran masyarakat terhadap perilaku hidup bersih dan sehat (PHBS), masih rendahnya komitmen pemerintah daerah (pemda) dalam pengelolaan sampah, lemahnya kelembagaan pengelola sanitasi (regulator dan operator) serta kemampuan sumber daya manusia. Pemerintah Indonesia masih perlu untuk belajar dari negara-negara lain yang telah berhasil dalam penyelenggaraan sistem pengelolaan sampah yang ramah lingkungan. Salah satu negara yang tergolong sukses dalam mengelola sampah adalah Korea Selatan. Studi dilakukan untuk membandingkan pengelolaan sampah di Indonesia dan Korea Selatan dilihat dari 5 aspek pengelolaan sampah, yaitu: aspek kelembagaan, aspek pembiayaan, aspek peraturan, aspek peran serta masyarakat, dan aspek teknis operasional. Penelitian dilakukan dengan melakukan studi literatur dan obervasi langsung ke Korea Selatan. Dari hasil penelitian disimpulkan bahwa sistem pengelolaan sampah di Indonesia masih ketinggalan dibandingkan dengan Korea Selatan, baik secara kelembagaan, sumber daya manusia, anggaran, penegakan hukum, serta partisipasi masyarakat dan swasta. Komitmen penuh dari seluruh stakeholder yang terkait merupakan faktor kunci dalam suksesnya penyelenggaranan pengelolaan sampah yang terintegrasi dan ramah lingkungan